The A-Z of social research a dictionary of key social science research concepts - Miller, Robert L. 1948-; Brewer, John D. (SAGE, 2003)
Alphabetically arranged in accessible, reader-friendly format this collection of 94 entries provides a concise introduction to the key concepts and methods in social research.